PENGARUH KETERAMPILAN DIGITAL, PENGALAMAN MAGANG, DAN KECERDASAN EMOSIONAL TERHADAP KESIAPAN KERJA MAHASISWA TINGKAT AKHIR PRODI MANAJEMEN UNIVERSITAS 17 AGUSTUS 1945 SURABAYA - Vera Tiara Ningrum; Sri Budi Kasiyati (Jurnal Ekonomi dan Bisnis, 2026)
This research is motivated by the low job readiness of students in the digital era that demands mastery of technology, practical experience, and emotional intelligence. This study aims to analyze the influence of digital skills, internship experience, and emotional intelligence on the job readiness of final year students of the Management Study Program, University of 17 August 1945 Surabaya. The research method uses a quantitative approach with multiple linear regression analysis on 143 respondents selected through a simple random sampling technique. The results show that the three variables have a positive and significant influence, both partially and simultaneously, on job readiness, with an Adjusted R Square value of 0.758. The conclusion of this study confirms that strengthening digital competencies, relevant internship experience, and emotional intelligence are important factors in improving student job readiness. Further research is recommended to add other variables to obtain more comprehensive results